Biological Treatment Advancements for the Remediation of Selenium from Wastewater - Singh V.; Tripathi G.; Mishra V. (My University, 2025)
Selenium (Se) is regarded as one of the essential micronutrients required by the living organism. However, bioaccumulation potential of Se makes it potentially a toxic element for the natural ecosystem and living organisms. Various anthropogenic and geologic actions such as mining-related activities, manufacturing activities, and volcanic eruption account for the selenium release in the environment. Recent pieces of research conducted in the field of water monitoring and quality assurance reported that selenium is a potential threat to environmental concern. Several physio-chemical techniques have been established for the remediation of selenium from wastewater, but the removal strategy based on biological process offers a cheaper alternative compared to the other methods. This chapter focuses on the biological treatment technologies utilizing bacteria, algae, fungi, and plant for the remediation of selenium-laden wastewater. It deals with the mechanism performed by the cells for the remediation of selenium from wastewater such as microbial reduction, biosorption, and volatilization. It also mentions the underlying principles of different biological reactors which are extensively studied for the treatment of selenium-laden wastewater. Biological treatment also offers an added advantage of the formation of elemental selenium nanospheres and nanorods exhibiting unique spectral and optical properties that finds its various applications in the field of electrical, manufacturing, and medical areas. © 2021 John Wiley & Sons Ltd. All rights reserved.